A comprehensive guide to sign language interpreting in Europe : 2012 edition - de Wit, Maya, 1968- (San Bernardino : M. de Wit, 2012)
Geft een overzicht van de status van tolken gebarentaal in Europa m.b.t. organisaties, werkgelegenheid, opleidingen en erkenning van gebarentaal. De publicatie is gebaseerd op de uitkomsten van een vragenlijst in 40 Europese landen en regio's.
Organizations: Establishment of sign language interpreter organization -- National organizations -- Names of the organizations -- Countries without an independent national interpreter organization -- Percentage of members -- Membership numbers -- Deaf interpreters as a member -- Non-interpreter membership to interpreter organizations -- Number of sign language interpreters based on membership percentage -- Membership fees -- Total membership fee per association -- Registry of interpreters. Education: Educational programs -- Countries and regions without a program -- New programs -- Length of the program -- Curricula -- Students enrolled in the interpreter training program. Employment: Intrpreters currently working -- Lack of interpreters -- Number of working interpreters: 2001 & 2004 & 2007 &2012. -- Deaf sign language users -- Deaf sign language users per interpreter -- The right to an interpreter -- Recognition of sign language -- Interpreters: forms of employment -- Responsible party for the payment of interpreting services -- Sign language recognition & funding of interpreting services -- Interpreting fees.
Keywords: Interpreters for the deaf -- Training of; Interpreters for the deaf -- Europe; Europe -- Interpreters for the deaf; Interpreters for the deaf -- Training of